2011
DOI: 10.1080/09640568.2010.528612
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth vs. land quality: a multidimensional approach in Italy

Abstract: This paper evaluates the recent economic dynamics in Italy and their implications for a specified environmental topic - land quality and its vulnerability to degradation. As opposed to the traditional economic literature, centred on GDP level and changes, a multidimensional concept of 'economic growth' was developed in the present study by considering several variables (share of agriculture and industry on the total production, labour productivity by sector, per capita value added) within a Principal Component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Alternatively or concurrently in other Mediterranean European countries, the degradation of ecosystem functions is linked to the opposite driver: rural abandonment (Weissteiner et al, 2011;García-Ruiz and Lana-Renault, 2011), which may take the form of cessation of agricultural activities or extreme extensification by conversion to minimum labor-and capital-intensive systems. This latter factor has been identified as a main driver for degradation of ecosystem services in Portugal (Pereira et al, 2004;Pereira et al, 2009;Teixeira, 2010), Spain (Cammeraat et al, 2007;Dunjó et al, 2003;Lesschen et al, 2007;Ruecker et al, 1999), Italy (Bathurst et al, 2003;d'Angeloa et al, 2000;Geeson et al, 2002;Salvati and Zitti, 2011), Greece (Juntti and Wilson, 2003) and France (Aronson et al, 2009). To establish a baseline for the future of ecosystem services from grazed landscapes, and depict the main drivers of change in the present, we use the Portuguese case.…”
Section: The Mediterranean Contextmentioning
confidence: 95%
“…Alternatively or concurrently in other Mediterranean European countries, the degradation of ecosystem functions is linked to the opposite driver: rural abandonment (Weissteiner et al, 2011;García-Ruiz and Lana-Renault, 2011), which may take the form of cessation of agricultural activities or extreme extensification by conversion to minimum labor-and capital-intensive systems. This latter factor has been identified as a main driver for degradation of ecosystem services in Portugal (Pereira et al, 2004;Pereira et al, 2009;Teixeira, 2010), Spain (Cammeraat et al, 2007;Dunjó et al, 2003;Lesschen et al, 2007;Ruecker et al, 1999), Italy (Bathurst et al, 2003;d'Angeloa et al, 2000;Geeson et al, 2002;Salvati and Zitti, 2011), Greece (Juntti and Wilson, 2003) and France (Aronson et al, 2009). To establish a baseline for the future of ecosystem services from grazed landscapes, and depict the main drivers of change in the present, we use the Portuguese case.…”
Section: The Mediterranean Contextmentioning
confidence: 95%
“…Institutional fragmentation of responsibilities in land-use planning also promoted urban sprawl [35,36]. The size of local government units may be important in the relationship with collective or individual actors (e.g., investors, landowners, stakeholders) [21,37,38].…”
Section: Political and Economic Forces Of Landscape Transformation Inmentioning
confidence: 99%
“…Our results suggest a ‘turning back’ to the economic geography of land resources when analysing the environment-economy relationship at the local scale [31]. We have demonstrated that a multidimensional approach is particularly suited to grasp the latent interconnection between the different components of socio-environmental systems.…”
Section: Discussionmentioning
confidence: 94%